Challenging chronocentrism: new approaches to futures thinking in the policy and praxis of widening participation in higher education. Issue 6 (17th August 2020) - Liveley, Genevieve; Wardrop, Alex
ABSTRACT: This paper examines one of the key temporal characteristics evident in public policy frames for widening participation in higher education. It demonstrates that the ambitions of such policies are potentially compromised by temporal notions implicated in a mode of chronocentrism, forecasting the future as a 'minimal departure' from the present. Engaging with the latest research into Futures Literacy and Anticipation it outlines alternative strategies for recognising and renegotiating such constraints ('What If?' scenarios and gaming), opening up pathways for policymakers and practitioners to imagine the future of higher education as a more inclusive and equitable time–space.